Evaluating the Frequency of Infertility in Retroverted Versus Anteverted Uterus Using Ultrasound - Sybil Rose, Rana Muhammad Athar Azeem Shams, Ambreen Sadaf, Sana Ali, Umair Ahsan (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To evaluate the frequency of infertility in retroverted versus anteverted uterus using ultrasound. Methods: The descriptive cross-sectional study was performed in total number of 380 patients using non-probability sampling technique. The study was conducted in the Department of Radiology, Tahir Medical Complex, Haroonabad in 6 months of duration. Married women of all age groups with anteverted and retroverted uterus were included in this study while all unmarried females were excluded from this study. The ultrasound was performed using VOLISON 730 with 3.5 MHz linear array broadband transducer on grayscale while patient positioning was supine. Results: Total 386 woman were enrolled and the mean age of the patient was 25 years with a range of 21-30±3.26 years. Out of 386 woman anteverted uterus was found in 134(34.7%) and anteflexed uterus was found in 2(0.5%). On the other hand, retroverted uterus was found in 86(22.3%) women and retroflex uterus was found and none of the women. Among 386 women, 142(36.8%) were nulliparous (P0), 107(27.7%) were primiparas (P1), 108(28%) were multiparas (P2) and 29(7.5%) were grand multiparas (P3). Primary fertility was diagnosed in 142(36.8%) women while secondary infertility was diagnosed in 244(63.2%). Conclusion: Secondary infertility was seen more frequently in anteverted uterus as compared with retroverted uterus.